Impact of a Serious Game (#RedPingüiNO) to Reduce Facial Self-Touches and Prevent Exposure to Pathogens Transmitted via Hands: Quasi-Experimental Intervention - Marta Arévalo-Baeza; Alejandro Viuda-Serrano; Carmen Juan-Llamas; Pablo Sotoca-Orgaz; Iván Asín-Izquierdo (JMIR Publications, 2023)
BackgroundAfter the COVID-19 pandemic, society has become more aware of the importance of some basic hygienic habits to avoid exposure to pathogens transmitted via hands. Given that a high frequency of touching mucous membranes can lead to a high risk of infection, it is essential to establish strategies to reduce this behavior as a preventive measure against contagion. This risk can be extrapolated to a multitude of health scenarios and transmission of many infectious diseases. #RedPingüiNO was designed as an intervention to prevent the transmission of SARS-CoV-2 and other pathogens through the reduction of facial self-touches by thoughtfully engaging participants in a serious game. ObjectiveFacial self-touches should be understood as behaviors of limited control and awareness, used to regulate situations of cognitive and emotional demands, or as part of nonverbal communication. The objective of this study was to ensure that participants become aware of and reduce these behaviors through a game of self-perception. MethodsThe quasi-experimental intervention was applied to 103 healthy university students selected by convenience sampling and put into practice for 2 weeks, with 1 control group (n=24, 23.3%) and 2 experimental groups (experimental group with no additional social reinforcement interventions: n=36, 35%; experimental group with additional social reinforcement interventions: n=43, 41.7%). The objective was to improve knowledge and perception and reduce facial self-touches to prevent exposure to pathogens transmitted via hands not only in health multihazard scenarios but also in ordinary circumstances. The ad hoc instrument used to analyze the experience consisted of 43 items and was valid and reliable for the purpose of this study. The items were divided into 5 blocks extracted from the theoretical framework: sociological issues (1-5); hygiene habits (6-13); risk awareness (14-19); strategies for not touching the face (20-26); and questions after the intervention (27-42), designed as a postintervention tool assessing the game experience. Validation of the content was achieved through assessment by 12 expert referees. External validation was performed using a test-retest procedure, and reliability was verified using the Spearman correlation. ResultsThe results of the ad hoc questionnaire, which were analyzed using the Wilcoxon signed-rank test and McNemar index to identify significant differences between test and retest for a 95% CI, showed that facial self-touches were reduced (item 20, P<.001; item 26, P=.04), and awareness of this spontaneous behavior and its triggers increased (item 15; P=.007). The results were reinforced by qualitative findings from the daily logs. ConclusionsThe intervention exhibited a greater effect from sharing the game, with interactions between people; however, in both cases, it was helpful in reducing facial self-touches. In summary, this game is suitable for reducing facial self-touches, and owing to its free availability and design, it can be adapted to various contexts.